2018
DOI: 10.1038/s41598-018-26573-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of a rare variant of the TNFSF13B gene with susceptibility to Rheumatoid Arthritis and Systemic Lupus Erythematosus

Abstract: A rare variant (BAFF-var) of the tumor necrosis factor superfamily 13b (TNFSF13B) gene has been recently associated with multiple sclerosis (MS) and systemic lupus erythematosus (SLE). The aim of this study was to investigate the association between TNFSF13B BAFF-var and susceptibility to rheumatoid arthritis (RA) and replicate that association in SLE. 6,218 RA patients, 2,575 SLE patients and 4,403 healthy controls from three different countries were included in the study. TNFSF13B BAFF-var was genotyped usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…Overexpression of the cytokine and drug target B-cell activating factor (BAFF; encoded by TNFSF13B) has been associated with susceptibility to SLE, multiple sclerosis and rheumatoid arthritis. The functional causal variant denoted as BAFF-var (a combination of rs374039502 and an insertion-deletion variant GCTGT→A [rs200748895]) has been initially identified by Genome Wide Association study (GWAS) in the Sardinian population and recently replicated in other cohorts of patients [78,79,144]. The BAFF-var is more frequent among Sardinians (MAF = 33%) than other populations (Europeans MAF = 3-5%) and was shown to yield a shorter transcript that escapes microRNA inhibition.…”
Section: Tnfsf13b/baffmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of the cytokine and drug target B-cell activating factor (BAFF; encoded by TNFSF13B) has been associated with susceptibility to SLE, multiple sclerosis and rheumatoid arthritis. The functional causal variant denoted as BAFF-var (a combination of rs374039502 and an insertion-deletion variant GCTGT→A [rs200748895]) has been initially identified by Genome Wide Association study (GWAS) in the Sardinian population and recently replicated in other cohorts of patients [78,79,144]. The BAFF-var is more frequent among Sardinians (MAF = 33%) than other populations (Europeans MAF = 3-5%) and was shown to yield a shorter transcript that escapes microRNA inhibition.…”
Section: Tnfsf13b/baffmentioning
confidence: 99%
“…RASopathies, which are caused by dominantly inherited mutations in several genes (KRAS, NRAS, PTPN11, RAF, SHOC2 and SOS1), are a group of neurodevelopmental disorders including Noonan syndrome (NS; OMIM 163950) and Noonan-related syndromes (NS2- 11;OMIM 605275, 609942, 610733, 611553, 613224, 613706, 615355, 616559, 616564, 618499). Beside classical phenotype patients with these disorders may present with features of SLE, autoimmune thyroiditis, vitiligo, celiac disease and Degos [79,145]. The affected proteins participate in the RAS/MAPK pathway that is involved in regulation of different cellular processes by transduction of growth factor signals [145].…”
Section: Rasopathiesmentioning
confidence: 99%
“…Autoimmune disorders, such as RA, are very heterogeneous and share symptoms, risk genes, comorbidities, and familial aggregation, suggesting a common genetic architecture that is extensively recognized in autoimmunity [66,67]. Several studies have revealed these shared genetics through simple comparisons of the associated genes [68], as was the case in a study conducted by our group, where González-Serna et al [69] considered the association of a rare variant in the TNFSF13B gene with RA and replicated this association in systemic lupus erythematosus (SLE) patients. TNFSF13B encodes the (B-cell activating factor) BAFF cytokine, which is essential for B-cell homeostasis and the regulation of B-cell maturation, differentiation, and survival [70].…”
Section: Shared Genetics In Autoimmunity and Drug Repurposingmentioning
confidence: 90%
“…Previous studies demonstrated that the frequency of the BAFF-var allele was higher among SLE patients from various European cohorts than among the corresponding control populations, a finding suggesting a relationship between the BAFF-var and SLE [17, 19]. The frequency of BAFF-var allele carriers (9.2%) and the MAF of the BAFF-var allele (4.6%) identified in our SLE study cohort were in line with and support the findings of case-control studies performed by González-Serna et al [19]. We detected the BAFF-var allele in 7.1% of SLE patients in our German cohort and the corresponding MAF was 3.69%.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of BAFF-var is notably elevated among patients with autoimmune diseases, such as multiple sclerosis, SLE, and rheumatoid arthritis. This fact implies a link between BAFF-var variant and susceptibility to autoimmune processes [17, 19]. However, to date the relationship between BAFF-var and SLE disease activity in specific organs has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%